Advances on circRNAs Contribute to Carcinogenesis and Progression in Papillary Thyroid Carcinoma - Xu, Xiaoqin; Jing, Jiexian (Frontiers in Endocrinology, 2021)
In view of the highly increased prevalence of papillary thyroid carcinoma (PTC) year by year, it’s of great importance to explore new molecular targets for anticancer strategy. Emerging evidence have indicated that circular RNAs (circRNAs), characterizeded by a closed loop structure and high stability, played important roles in tumorigenesis and development of human cancer by regulating multiple complex biological processes, like cellular proliferation, metastasis, and metabolism. . Comprehensive understanding of the roles of circRNAs will facilitate the development of future promising therapeutic strategies for treating cancers, including PTC. In this paper, we reviewed the profile of circRNA in PTC, its regulatory roles and the pathological mechanism, as well as their related clinical significance. Meanwhile, challenges of this specific field were discussed.